Investigation of tire derived aggregate as a fill material for highway embankment. Issue 2 (April 2014) - Meles, Daniel; Bayat, Alireza; Hussien Shafiee, Mohammad; Nassiri, Somayeh; Gul, Mustafa
<x content-type="archive" xml:space="preserve">Abstract</x> This study investigates the compression behavior and performance of tire derived aggregate (TDA) used to construct an 80-m long embankment for a highway test road in Edmonton, AB, Canada. The road contained four test sections made from passenger and light truck tires (PLTT), off-the-road (OTR) truck tires, TDA–soil mixture, and native soil. A total of 30 temperature probes and 25 settlement plates were embedded into the road to monitor the embankment. Falling Weight Deflectometer (FWD) test was also conducted under different load levels to determine the embankment material's deflection behavior after the placement of the soil cover. Through observation, field data, and FWD testing, it was determined that PLTT is more compressible than OTR and the TDA–soil mixture, and TDA–soil mix section showed equivalent performance with the control section. Additionally, all the temperature probes revealed no internal heating during the 8-month monitoring period.